Operacijsko zdravljenje raka debelega črevesa in danke na Oddelku za abdominalno kirurgijo Splošne bolnišnice Maribor leta 2000 - Ivanecz, Arpad (Zdravniški vestnik, 2003)
Background. To obtain information on the surgical treatment of patients with colorectal cancer at the Department of Abdominal Surgery, in the General Hospital Maribor, in the year 2000. Mathods. Using a computerized protocol, we prospectivelly colect and registrate data about patients with colorectal cancer. Our data contains preoperative diagnostic investigations, intraoperative findings, pathohistological examinations after surgery, operative morbidity and mortality and alternations, found during follow up examinations. Results. In the year 2000, 135 patients (72 male and 63 female) with colorectal cancer underwent surgery. The average age was 66.4 years, spanning from 39 to 90 years. 15% were presented as emergencies. The general operability rate was 99%, the resectability rate was 92% and the portion of potentially curative resections was 69%. Cases were localised into right-sided (23%), transverse (2%), left-sided (32%) and rectal (43%). The stage distribution according to the TNM classification was as follows: Stage 0: 1 patient, Stage I: 17%, Stage II: 42%, Stage III: 19%, Stage IV: 22%, 5 patients were undefined. The portion of different surgical procedures is presented in the text. The postoperative mortality rate was 6%, 7 patients died after urgent procedures and 1 died after elective surgery. The rate of surgical complications, which required reoperation was 4.4%. The rate of conservativelly treated surgical complications was 6.6%. The average hospital stay was 12.8 days and ranged from 6 to 36 days. Conclusions. The number of surgically treated patients with colorectal cancer in our institution is growing every year like in other departments in Slovenia and western countries. The rate of potentially curative resections can be expanded by early detection of the disease, as well as with more accurate pre- and intraoperative staging of the tumor, and consideration of the modern principles of management.
Keywords: Colorectal neoplasms; Kirurški postopki, operativni; Novotvorbe, kolorektalne; Surgical procedures, operative